Oxford international primary English workbook 5 - Barber, Alison (oxford Oxford university press, 2021)
The *Oxford International English Workbook 5* is a comprehensive resource designed to enhance English language learning for students at an intermediate level. It complements the core textbook by offering a range of engaging activities that reinforce grammar, vocabulary, reading, and writing skills. The workbook encourages critical thinking and creativity through diverse exercises, aligned with global contexts and themes. It supports independent learning while preparing students for advanced language challenges.